In Vitro Interaction between Cultured Cells and Human Blood Platelets - Holme, Randi; Oftebro, Reidar; Hovig, Torstein (Thrombosis and Haemostasis, 1978)
The effects of washed human cultured cells (tumour cells and Chang liver cells) on human blood platelets in heparinized plasma were studied. Platelet aggregation was induced by suspensions of the tumour cells. Ultrastructural examination showed that the platelets, especially in the central regions of the aggregates, were tightly packed and the α-granules were mostly present. In the periphery of the aggregates the platelets appeared swollen and devoid of organelles, and fibrin strands were seen. The platelet aggregation was not completely abolished by incubation with apyrase. The washing fluids from the tumour cells also induced platelet aggregation, but the aggregation could be abolished by incubation with apyrase.When three different lines of the Chang cells were used, suspensions of two lines of these cells induced platelet aggregation, but the third line did not. Presence of ADP could be demonstrated in the washing fluids from the cultured cells, except for the one line of Chang cells which did not induce platelet aggregation. The experiments indicated that the platelet aggregation induced by the various types of cells was mediated via ADP, but with a possible additional effect of coagulation activity.